Increased Levels of Oxidative Stress Markers, Soluble CD40 Ligand, and Carotid Intima-Media Thickness Reflect Acceleration of Atherosclerosis in Male Patients with Ankylosing Spondylitis in Active Phase and without the Classical Cardiovascular Risk Factors. (15th August 2017) - Stanek, Agata; Cholewka, Armand; Wielkoszyński, Tomasz; Romuk, Ewa; Sieroń, Karolina; Sieroń, Aleksander
Abstract : Objective . The primary aim of the study was to assess levels of oxidative stress markers, soluble CD40 ligand (sCD40L), serum pregnancy-associated plasma protein-A (PAPP-A), and placental growth factor (PlGF) as well as carotid intima-media thickness (IMT) in patients with ankylosing spondylitis (AS) with active phase without concomitant classical cardiovascular risk factors. Material and methods . The observational study involved 96 male subjects: 48 AS patients and 48 healthy ones, who did not differ significantly regarding age, BMI, comorbid disorders, and distribution of classical cardiovascular risk factors. In both groups, we estimated levels of oxidative stress markers, lipid profile, and inflammation parameters as well as sCD40L, serum PAPP-A, and PlGF. In addition, we estimated carotid IMT in each subject. Results . The study showed that markers of oxidative stress, lipid profile, and inflammation, as well as sCD40L, PlGF, and IMT, were significantly higher in the AS group compared to the healthy group. Conclusion . Our results demonstrate that ankylosing spondylitis may be associated with increased risk for atherosclerosis.